Chemiluminescence method for evaluating photooxidative degradation of dispensed drugs: a potential new drug information tool - Yuriko Murai; Kasumi Kudo; Hiroyuki Suzuki; Taisuke Konno; Yasuyuki Agatsuma; Hitoshi Nakamura (BMC, 2024)
Abstract Background Dispensed drugs stored by patients are often in single-dose packages (SDPs) or are crushed and mixed after being removed from a press-through package (PTP) sheet. Information on their stability is extremely limited. To address this, we explored using chemiluminescence (CL) measurements to detect oxidative degradation. Methods Eight amlodipine, 14 telmisartan, and two warfarin preparations were used as specimens. These preparations were stored at room temperature under various conditions, after which CL was measured. Cellopoly packaging paper was used for SDP. Three light conditions were used (Condition A: darkness, Condition B: indoor diffused light (approximately 400 lx), and Condition C: exposure to 4,000 lx). CL cumulative light output was measured every minute under nitrogen gas conduction and with a sample chamber temperature of 150 °C, for a maximum of 10 min. Luminescence images were obtained simultaneously with the CL measurements. Results CL was observed on light-exposed tablet surfaces. For each preparation, an increase in the CL value was observed with the duration of light exposure. In the same preparation with the same exposure time, CL tended to be higher in the order of Condition A < B < C. Moreover, CL increased even when no changes in color were observed by the naked eye. A comparison between preparations with the same main ingredients showed differences in the rate of increase in CL with exposure, and each was found to show a different reactivity to light. Conclusions To the best of our knowledge, this is the first study to visually capture the surface oxidation of tablets exposed to light using the CL method. The CL values, thought to be derived from photooxidation, increased with exposure of tablets and powders to light after SDP. This method can sensitively assess drug degradation due to photooxidation. Further research is needed to establish a CL method for assessing the stability of preparations in clinical settings.